Cutting performance of cemented carbide cutting tool in turning high‐density fiberboard. Issue 12 (10th December 2018) - Zhu, Z.; Cao, P.; Guo, X.; Qiu, X.; Xie, S.; Ekevad, M.
Abstract: In order to provide a scientific and reliable guidance for wood processing industry, the effects of cutting parameters on cutting forces, cutting temperature and tool wear were studied when turning high‐density fiberboard by use of cemented‐carbide cutting tools. The results showed that cutting forces (normal force and radial force) and cutting temperature are not affected by the cutting parameters in the same way: cutting forces decrease with increasing spindle speed, whereas cutting temperature increase with an increase of the spindle speed. However, there is a positive relation for cutting forces and temperature, to the feed per turn when cutting. The wear of the cemented‐carbide cutting tool is shown by two mechanisms: Mainly adhesive wear but also abrasive wear, showed by loss of carbide‐grains and by cracking and chipping, respectively. This study also indicated that higher‐speed cutting is beneficial for wood‐processing; evident by reduced energy for cutting and higher efficiency in production.